Relationship Facilities are Available with Community Interests in Utilizing TBM in the PKBM Tapakis Cerdas - Ihsani, Fikrul; Syuraini, Syuraini (Universitas Negeri Padang, 2019)
The background of this research, namely the low interest of the community in utilizing TBM (TBM) in PKBM Tapakis Cerdas, this is allegedly related to the incomplete facilities available in TBM PKBM Tapakis Cerdas. The purpose of this research is to describe: (1) facilities available in TBM PKBM Tapakis Cerdas, (2) community interest in utilizing TBM in PKBM Tapakis Cerdas, and (3) the relationship between available facilities and community interest in utilizing TBM in PKBM Tapakis Cerdas. This type of research, namely correlational quantitative research with a population of all people registered with TBM, people who have visited TBM at least twice in 2018, amounting to 24 people, and the entire population used as a sample called respondents. The sampling technique in this study, the census method. While the data collection technique uses a questionnaire, and the data collection tool uses a questionnaire. Data analysis techniques using the calculation of percentages and Rank Order Correlation. The results of the study stated that: (1) the facilities available at TBM PKBM Tapakis Cerdas were in the incomplete category, (2) community interest in utilizing TBM in PKBM Tapakis Cerdas was in a low category, (3) There was a significant relationship between the facilities available with community interest in utilizing TBM in PKBM Tapakis Cerdas. Based on the results of the study it is recommended that TBM managers in PKBM Tapakis Cerdas further enhance and equip facilities at TBM.Keywords: Facilities, Interests, Community Reading Park